Vertical and bevel-structured SiC etching techniques incorporating different gas mixture plasmas for various microelectronic applications - Ho-Kun Sung (Nature Portfolio, 2017)
Abstract This study presents a detailed fabrication method, together with validation, discussion, and analysis, for state-of-the-art silicon carbide (SiC) etching of vertical and bevelled structures by using inductively coupled plasma reactive ion etching (ICP-RIE) for microelectronic applications. Applying different gas mixtures, a maximum bevel angle of 87° (almost vertical), large-angle bevels ranging from 40° to 80°, and small-angel bevels ranging from 7° to 17° were achieved separately using distinct gas mixtures at different ratios. We found that SF6 with additive O2 was effective for vertical etching, with a best etching rate of 3050 Å/min. As for the large-angle bevel structures, BCl3 + N2 gas mixtures show better characteristics, exhibiting a controllable and large etching angle range from 40° to 80° through the adjustment of the mixture ratio. Additionally, a Cl2 + O2 mixture at different ratios is applied to achieve a small-angel bevels ranging from 7° to 17°. A minimum bevel angel of approximately 7° was achieved under the specific volume of 2.4 sccm Cl2 and 3.6 sccm O2. These results can be used to improve performance in various microelectronic applications including MMIC via holes, PIN diodes, Schottky diodes, JFETs’ bevel mesa, and avalanche photodiode fabrication.